Evaluation of the neuroprotective efficacy of the gramine derivative ITH12657 against NMDA-induced excitotoxicity in the rat retina - Di Pierdomenico, Johnny; Gallego-Ortega, Alejandro; Norte-Muñoz, María; Vidal-Villegas, Beatriz; Bravo, Isaac; Boluda-Ruiz, María; Bernal-Garro, Jose Manuel; Fernandez-Bueno, Iván; Pastor-Jimeno, Jose Carlos; Villegas-Pérez, María Paz; Avilés-Trigueros, Marcelino; de los Ríos, Cristobal; et al. (Frontiers in Neuroanatomy, 2024)
• Administration of 10 mg/kg ITH12657, starting 12 hours before NMDA injection and dispensed for 3 days, resulted in the best significant protection of Brn3a+RGCs against NMDA-induced excitotoxicity • ITH12657-treatment showed a significant preservation of retinal thickness when compared to vehicle-treament• Treatment with ITH12657 resulted, in smaller reductions of pSTR and b-wave amplitudes compared to those treated with vehicle, indicating that ITH12657 treatment offered functional protection against NMDA-induced retinal excitotoxicity • ITH12657 afforded a significant protection against NMDA-induced excitotoxicity for the populations of Brn3a+RGC, αRGC, and αONs-RGC, but not for the population of αOFF-RGC